Importance of the time of initiation of mineralocorticoid receptor antagonists on risk of mortality in patients with heart failure. (March 2015) - Rossi, Rosario; Crupi, Nicola; Coppi, Francesca; Monopoli, Daniel; Sgura, Fabio
Introduction: Several studies have definitively shown the benefit of mineralocorticoid receptor antagonists (MRAs) in patients with heart failure (HF). However, very few prior studies examined the relationship between the timing of initiation of MRAs and prognosis. In addition, on this topic, there is no information regarding the specific population of patients suffering a first episode of decompensated congestive HF. Methods: We studied a homogenous cohort of patients discharged alive from our hospital after a first episode of decompensated congestive HF, in order to clarify the association between time of aldosterone receptor antagonist (ARA) initiation (within the first 90 days after hospital discharge) and mortality. Our population was composed of a series of consecutive patients. All-cause mortality was compared between patients who initiated MRAs at discharge (early group) and those who initiated MRAs one month later and up to 90 days after discharge (delayed group). We used prescription time distribution matching to control for survival difference between groups. Results: The early and delayed groups consisted of 365 and 320 patients, respectively. During the one-year follow-up, a significant difference in mortality was demonstrated between groups. Adjusted hazard ratios (HRs) for early versus delayed initiation were 1.72 (95% confidence interval (CI) 0.96 to 2.84) at six months, and 1.93 (95% CI 1.18 to 3.14) at one year. Conclusions: Delay of MRA initiation up to 30 to 90 days after discharge implies a significant increase in mortality compared with MRA initiation at discharge, after a first episode of decompensate congestive HF.